Mass detectability in dedicated breast CT: A simulation study with the application of volume noise removal - Xia, J.Q.; Lo, J.Y. (2008 8th IEEE International Symposium on BioInformatics and BioEngineering, 2008)
Dedicated breast Computed Tomography (CT) is an emerging new technique for breast cancer imaging. Breast CT data can be acquired at a dose level as low as the conventional two-view mammography. Since the dose is equally split into hundreds of projection views, each projection image contains non-ignorable quantum noise. This study is aimed at investigating how volume noise removal affects the mass detectability in breast CT. A Partial Diffusion Equation (PDE) based denoising technique was applied before the reconstruction of either a simulated breast volume embedded with a contrast-detail mass phantom or a real human subject breast CT volume embedded with a simulated spherical mass. By applying a mathematical observer, it is found that the PDE volume noise removal technique improves the mass detectability in breast CT in a statistically significant sense.